The historical development of museology in Turkey - Erbay, Fethiye. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2019., 2019)
The historical development of Turkish museology after 1980 will be re-searched in this thesis. The changes that happened before and after 1980 will be examined. The legal arrangements made after 1980 constitute the turning point for Turkey's museology. Law no. 2863 Code of Protection of Cultural and Natural Properties marks a drastic change in Turkish museology. "Regulation on Private Museums and Their Auditing", published in the Official Gazette (no. 18289, 22 January 1984) allowed for the establishment of private museums. The number and variety of private museums has in-creased considerably since 1980. In 2000, the development of modern museology has brought new muse-um practices that are open to scientific applications and research. The architectural structures of the museums, exhibition aspects, and technology and management models have changed. After 2010, the number of the city, science, and university museums has increased. In addition, international exhibitions and museum awards that came with the membership to international organizations have created new sources for the change in the museum culture. With advancing technology, the museum exhibition and presentation techniques have become more visitor-oriented. The use of touch screens, simulators, robots and, holograms in the exhibition areas have supported the modern new museology. The number of digital, mobile, and visual museums has increased rapidly. The increasing interest in the muse-ology in the culture industry and creative industries has led to a change in perception in the society. However, this has caused a lot of controversies about the sustainability of the development of the museums in Turkey. This thesis tries to contribute to the ongoing discussions.
Keywords: Museum techniques -- History.; Museum techniques -- Turkey.